Trends of Autologous Free-Flap Breast Reconstruction and Safety during the Coronavirus Disease 2019 Pandemic - Elmer, Nicholas A.; Bustos, Valeria P.; Veeramani, Anamika; Hassell, Natalie; Comer, Carly D.; Manstein, Samuel M.; Kinney, Jacquelyn; Lee, Bernard T.; Lin, Samuel J. (Journal of Reconstructive Microsurgery, 2023)
Background Autologous free-flap breast reconstruction (ABR) is a valuable surgical option for patients following mastectomy. The coronavirus disease 2019 (COVID-19) pandemic has led to a myriad of factors that have affected access to care, hospital logistics, and postoperative outcomes. This study aims to identify differences in patient selection, hospital course and severity, and postoperative outcomes for patients who underwent ABR during and prior to the COVID-19 pandemic.Methods Patients undergoing ABR from the American College of Surgeons National Surgical Quality Improvement Program 2019 to 2020 database were analyzed to compare sociodemographics, hospital course, and outcomes over the first postoperative month. Multivariable logistic regression was used to identify factors predictive of complications based on the operative year.Results In total, 3,770 breast free flaps were stratified into two groups based on the timing of reconstruction (prepandemic and pandemic groups). Patients with a diagnosis of disseminated cancer were significantly less likely to undergo ABR during the COVID-19 pandemic. On univariate analysis, there were no significant differences in postoperative complications between the two groups. When controlling for potentially confounding sociodemographic and clinical risk factors, the COVID-19 group was significantly more likely to undergo reoperation compared with the prepandemic group (p < 0.05).Conclusion When comparing outcomes for patients who underwent ABR prior to and during the COVID-19 pandemic, we found a significant increase in the odds of reoperation for those who had ABR during the pandemic. Debridement procedures and exploration for postoperative hemorrhage, thrombosis, or infection increased in the prepandemic group compared to the COVID-19 group. Notably, operative times decreased.
Keywords: autologous breast reconstruction; free-flap reconstruction; COVID-19